MON-394 Vitamin D Levels and Functional Recovery Following Hip Fracture - Mohan, Sneha (J Endocr Soc, 2020)
Background: Vitamin D deficiency is common in patients presenting with low energy hip fractures. The relationship between Vitamin D levels at the time of a fracture with long term functional outcomes has not been studied. Identifying a benefit to recovery with adequate vitamin D would support supplementation in elderly patients at risk for hip fracture. Methods: A retrospective cohort of patients >/= 50 years, who were treated surgically for low energy hip fracture between July 1 2016 and June 30 2018 were identified. The correlation between Vitamin D levels and functional recovery, assessed using the time up and go (TUG) test, survival at 3 months and 1 year, and readmission within 3 months was examined. The Charlson comorbidity index (CCI) at baseline was also assessed. Results: A total of 216 patients were treated for a hip fracture of which 174 were included with measured baseline Vitamin D levels. A majority were female (112, 64.4%), mean age 79.6 years (+/-11.9), mean Vitamin D level 28.2 ng/ml (+/- 12.4) and mean CCI 5.9 (+/- 2.5). Vitamin D <20 ng/ml was seen in 39 (22.4%) patients and all received appropriate supplementation. 39 (22.4%) individuals died within a year of surgery, among whom 17 (43.6% of 39) passed away within 3 months. 36 (20.7%) were readmitted within 3 months of surgery and 14 (8%) sustained a second fracture within a year. The correlation of Vitamin D levels, taken as a continuous variable, to outcomes, was analyzed using logistic regression. Although not significant, higher Vitamin D was found to be protective against death within 3 months (OR=0.995, p=0.8), but actually increased the odds of death within 1 year (OR=1.008, p=0.62), readmission within 3 months (OR=1.001, p=0.96), second fracture within 1 year (OR=1.017, p=0.33) and failure to recover (OR=1.002, 0.86). After adjusting for age, gender and CCI, Vitamin D levels were non-significantly inversely associated with both TUG 1 and TUG2, with every 1 unit higher Vitamin D associated with a TUG lowered by 0.15 seconds, p=0.42 and 0.44. Vitamin D was poorly correlated to CCI with correlation coefficient of 0.02, p = 0.71. Conclusions: Our results indicate that Vitamin D levels at the time of a hip fracture do not correlate with patients’ functional outcomes. It is possible that replacing vitamin D eliminated the possible negative impact on functional recovery.